Classification of skin sensitizing substances: a comparison between approaches used by the DFG-MAK Commission and the European Union legislation - Lessmann, Holger; Uter, W.; Diepgen, Thomas L.; Drexler, H.; Fartasch, M.; Greim, H.; Hartwig, A.; Kreis, P.; Löser, E.; Merget, R.; Merk, H.; Nowak, D.; et al. (Regulatory toxicology and pharmacology, 2011)
A systematic classification of substances (or mixtures of substances) with regard to various toxicological endpoints is a prerequisite for the implementation of occupational safety strategies. As its principal task the “Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area” of the “Deutsche Forschungsgemeinschaft” (DFG-MAK Commission) derives and recommends maximum workplace concentrations and biological tolerance values (MAK and BAT values) based exclusively on scientific arguments. Several endpoints are evaluated separately in detail, e.g. carcinogenicity, risks during pregnancy, germ cell mutagenicity or contribution to systemic toxicity after cutaneous absorption. Skin- and airway sensitization is also considered; the present paper focuses on these two endpoints.